Evaluation of the Non-Cash Food Assistance Program in Sadang Village, Sucinaraja District, Garut Regency - Ikeu Kania (ijd-demos, 2022)
AbstractThis study aims to determine the evaluation of the Non-Cash Food Assistance program, now on known as BPNT, in Sadang Village, Sucinaraja District, Garut Regency, and the factors that influence it. The use of the qualitative method as the research method was selected using descriptive analysis. In collecting data, the method used was interviews with selected informants, observation, and documentation. Data analysis techniques employ data reduction, data presentation, and concluding. In terms of the effectiveness of the Beneficiary Families, from now on, known as KPM, it was concluded that they felt the benefits: Non-Cash Food Assistance, known as BPNT. In terms of efficiency, errors in targeting targets in the distribution of BPNT can lead to budget leakage. In terms of the distribution of BPNT, it is carried out following the portion. In terms of accuracy, KPM expects the program to continue. The enumerator's subjectivity is high in recording poor households in terms of efficiency. In terms of responsiveness, BPNT implementers at each level understand enough about BPNT's activities as there are several inhibiting factors in the field. Suggestions put forward by researchers are updating data and data validity of BPNT recipients every six months by BPNT assistants in coordination with RT, RW. The assistant regularly checks people who are no longer entitled to receive BPNT. Socialization to KPM who are already prosperous wants to leave BPNT membership.Keywords: Non-Cash Food Aid, Evaluation, Program, Beneficiary Family. AbstrakPenelitian ini bertujuan untuk mengetahui evaluasi program Bantuan Pangan Non Tunai yang sekarang disebut BPNT, di Desa Sadang, Kecamatan Sucinaraja, Kabupaten Garut, dan faktor-faktor yang mempengaruhinya. Penggunaan metode kualitatif sebagai metode penelitian dipilih dengan menggunakan analisis deskriptif. Dalam pengumpulan data, metode yang digunakan adalah wawancara dengan informan terpilih, observasi, dan dokumentasi. Teknik analisis data menggunakan reduksi data, penyajian data, dan penarikan kesimpulan. Dari sisi efektivitas Keluarga Penerima Manfaat (KPM), mulai saat ini yang dikenal dengan KPM disimpulkan bahwa mereka merasakan manfaat: Bantuan Pangan Non Tunai yang dikenal dengan BPNT. Dari sisi efisiensi, kesalahan penargetan target dalam pendistribusian BPNT dapat menyebabkan kebocoran anggaran. Dalam hal penyaluran BPNT dilakukan mengikuti porsinya. Dari sisi akurasi, KPM berharap program ini terus berlanjut. Subyektivitas pencacah tinggi dalam mencatat rumah tangga miskin dari segi efisiensi. Dari sisi ketanggapan, para pelaksana BPNT di setiap tingkatan cukup memahami kegiatan BPNT karena ada beberapa faktor penghambat di lapangan. Saran yang diajukan peneliti adalah pemutakhiran data dan validitas data penerima BPNT setiap enam bulan sekali oleh pendamping BPNT berkoordinasi dengan RT, RW. Pembantu tersebut secara rutin memeriksa orang-orang yang tidak lagi berhak menerima BPNT. Sosialisasi kepada KPM yang sudah sejahtera ingin keluar dari keanggotaan BPNT.Kata kunci: Bantuan Pangan Non Tunai, Evaluasi, Program, Keluarga Penerima Manfaat.